GIS and regional development: Examples of applications - Rui Pedro Juliao (European Regional Science Association (ERSA), 1998)
The recent development of Geographic Information Technologies (GIT), such as GIS, Remote Sensing and Desktop Mapping gives to the technicians of landscape management and regional development areas, access to a new powerful set of tools with an high potential for spatial analysis. Our project's ambition is to confirm that GIT can be useful tools for the definition and management of development policies. The ability of GIT to analyse geographical information (more or less 80 to 90% of the overall information that exists can be georeferenced) will create conditions to establish a model for economical development and with the support of this model decisions can be more accurate. By doing so, we will encourage the use of GIS in the regional science field. The results that we already had achieved with our project push us in front. That's why it is important to present them. In order to gather more people for this area. This paper will resume the activities and the major conclusions of some projects being developed since 1996 with the main purpose of establishing a theoretical background and create sample methodologies to support economic development through the use of GIS.
Keywords: 330